The effect of the three-way dialogue strategy using educational tools on learning the skills of head handling and dribbling in handball for students - Al-Obaidi, Raghad Ali Hussein Ali (Sulaimani Journal for Humanities, 2025)
This research aims to identify the effectiveness of a three-way dialogue strategy, using educational tools, in teaching students the overhead and dribbling skills in handball. It also seeks to determine the relative effectiveness of the experimental and control groups in the post-test for learning these skills. The researcher employed an experimental approach, deemed suitable for the research problem, with a two-group (experimental and control) design using pre- and post-tests. The research population consisted of 60 fourth-grade students at Al-Khamayel Preparatory School for Boys in Al-Shomali District, Al-Hashimiya Education Department, Babil Governorate Directorate of Education, during the 2023-2024 academic year. A sample of 40 students was selected, divided into two groups of 20 each: an experimental group and a control group. The research also aims to identify the effectiveness of this three-way dialogue strategy, utilizing educational tools, in teaching students the overhead and dribbling skills in handball. Six educational units were developed using the three-step dialogue strategy (initiative, response, and evaluation) to teach two handball skills: overhead passing and dribbling. The units were delivered over three weeks, with two units per week, each lasting 45 minutes. The research concluded that using the three-step dialogue strategy and its associated teaching aids effectively increased student motivation to learn overhead passing and dribbling, fostering self-reliance and interaction with peers through the strategy's three steps (initiative, response, and evaluation). Furthermore, the three-step dialogue strategy enhanced social and educational relationships among students and between students and their teachers. The researcher recommends several measures, including the continued use of the three-step dialogue strategy in teaching handball skills to students and the implementation of modern teaching strategies due to their positive impact on learning outcomes.